2004
DOI: 10.1111/j.1572-0241.2004.30390.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Erosive Esophagitis: A Multivariate Analysis Based on the ProGERD Study Initiative

Abstract: Some patient-associated factors increase the risk of erosive esophagitis as opposed to nonerosive reflux disease. However, no single factor or combination of factors is capable of predicting mucosal damage with clinically sufficient certainty. Thus, endoscopy is still required in all GERD patients if valid information on the state of the esophageal mucosa is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
135
4
15

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(177 citation statements)
references
References 20 publications
23
135
4
15
Order By: Relevance
“…Th e ProGERD study, likely the largest of its kind ( > 5,000 patients) used logistic regression analysis to identify several independent risk factors for ERD. Th e odds for higher degrees of ERD increased as BMI rose ( 18 ). It is of greatest concern that there has been a well-documented association between BMI and carcinoma of the esophagus and gastric cardia ( 19 ).…”
Section: Symptoms and Epidemiologymentioning
confidence: 99%
“…Th e ProGERD study, likely the largest of its kind ( > 5,000 patients) used logistic regression analysis to identify several independent risk factors for ERD. Th e odds for higher degrees of ERD increased as BMI rose ( 18 ). It is of greatest concern that there has been a well-documented association between BMI and carcinoma of the esophagus and gastric cardia ( 19 ).…”
Section: Symptoms and Epidemiologymentioning
confidence: 99%
“…4,6 Patients can progress from NERD to ERD, even on proton-pump inhibitor (PPI) therapy, but progression from ERD to BE is uncommon and from NERD to BE is very uncommon. [7][8][9] Labenz et al reported on the progression of GERD (ProGERD) study of 3,894 patients with GERD who underwent baseline endoscopy and repeat endoscopy at 2 years. 8 As is characteristic of a disease spectrum, many patients had progressed or regressed from one GERD stage to another.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first prospective population-based study to explore an association between chronic HBV infection and GERD. The increased incidence of GERD in HBV carriers was independent of other known risk factors [16][17][18]. Moreover, we found a differential association between genders and APRI levels, and chronic HBV infection was an independent risk factor of erosive esophagitis, especially in female subjects and Data are shown by mean ± standard deviation or proportion of the character P \ 0.05 is considered as statistical significance those with higher APRI levels.…”
Section: Discussionmentioning
confidence: 76%